2017
DOI: 10.1186/s12886-017-0451-1
|View full text |Cite
|
Sign up to set email alerts
|

24-month clinical outcomes of a treat-and-extend regimen with ranibizumab for wet age-related macular degeneration in a real life setting

Abstract: BackgroundTo evaluate the clinical effectiveness and analyze the outcomes of a treat-and-extend (T&E) treatment regimen with ranibizumab for wet age-related macular degeneration (ARMD) in real life clinical settings over the first 2 years (24 months) of treatment.MethodsRetrospective analysis of visual acuity, spectral domain optical coherence tomography (SD-OCT) parameters and treatment burden data of 56 eyes of 54 unselected treatment naive patients diagnosed with exudative ARMD. Monthly injections were offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…If one of the two drugs would show a clear advantage over the other in terms of risk and treatment burden recommendations and clinical practice guidelines should be adapted accordingly. Currently, two alternative treatment strategies are gaining popularity among retina specialists [ 9 ]. As opposed to fix monthly or bimonthly injection schemes, Pro re nata (PRN) means that injections are carried out as needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If one of the two drugs would show a clear advantage over the other in terms of risk and treatment burden recommendations and clinical practice guidelines should be adapted accordingly. Currently, two alternative treatment strategies are gaining popularity among retina specialists [ 9 ]. As opposed to fix monthly or bimonthly injection schemes, Pro re nata (PRN) means that injections are carried out as needed.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to fix monthly or bimonthly injection schemes, Pro re nata (PRN) means that injections are carried out as needed. The Treat & Extend (T&E) protocol is based on the response to the last injection and decision to reduce or prolong injection intervals is being taken accordingly [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health professionals may also wish to update their core knowledge on the current status of the published literature on the T&E regimen in nAMD. A detailed review of these publications is beyond the scope of this article but we have provided a convenient summary in Table 1 of the 15 key publications 10 , 11 , 16 , 32 , 34 37 , 39 , 41 46 in this field. However, it is worth highlighting that a recent systematic review on T&E in nAMD by Rufai et al ana-lyzed the outcomes of 748 eyes from nine studies and found mean VA gain of 8.92 letters with a mean of 8.60 injection at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Since the change of licensed posology to a Treat-and-Extend (T&E) regimen for ranibizumab therapy in 2015 in the UK and 2012 in other countries, 9 there has been an emerging body of evidence reporting better visual outcomes with the T&E approach than with the PRN regimen in a real-world setting. 10 14 …”
Section: Introductionmentioning
confidence: 99%
“…12,[14][15][16][17][18][19][20][21][22] Additionally, there is an emerging body of evidence reporting better visual outcomes with the T&E regimen than PRN in various real-world studies. [23][24][25] In a meta-analysis of over 25,000 patients with nAMD the mean change in VA for patients receiving T&E was +8.8, +6.7, and +5.4 Early Treatment Diabetic Retinopathy Study (ETDRS) letters at year 1, year 2, and ≥3 years, respectively. In comparison, patients treated with PRN had +3.5, +1.3, and −1.9 ETDRS letters at the same time intervals.…”
Section: Clinical Namd Trials Utilising the Tande Regimenmentioning
confidence: 99%